SISTEM MATA PENCAHARIAN DAN KEGIATAN EKONOMI MASYARAKAT BADUY LUAR DI LEBAK, BANTEN: TRADISI DAN DINAMIKA MODERNISASI - Hernawati; Sapriya; Encep Supriatna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the livelihood systems and economic activities of the Outer Baduy community in Lebak, Banten, Indonesia. Known for their rich traditions and cultural heritage, the Outer Baduy are navigating the balance between preserving ancestral values and adapting to modernization. Their livelihoods primarily depend on traditional agriculture and handicrafts, such as weaving Baduy textiles, which are not only functional but also carry cultural significance. The research employs a qualitative case study approach, collecting data through in-depth interviews, participant observations, and document analysis. The findings reveal that while the Outer Baduy community benefits from economic opportunities in tourism and local trade, they face challenges in maintaining their cultural identity amidst external influences. This study underscores the community's resilience in integrating sustainable practices and preserving cultural integrity in the face of modern economic demands.